PRIVATE SECURITY BUSINESS/ DOMAIN IN INDIA (IMPACT ON MILITARY VETERANS’ EMPLOYMENT) - Sakerwala, Husein (Digital Repository of Theses, 2023)
According to the Federation of Indian Chambers of Commerce and Industry (FICCI), the Indian private security market was estimated at INR 99,000 crore (~USD 15.2 billion) by 2020 and is likely to touch INR 1.5 lakh crores (~USD 23.1 billion) by 2025 (as per latest industry estimates). As per the Ministry of Defence Annual Report (2018) and Director General Resettlement Report (2022), nearly 60,000 armed forces personnel retire or are released from active service every year. Most of them are in the comparatively younger age bracket of 35 to 45 years and need a second career to support their families. The availability of trained and experienced manpower like military veterans, looking for a second career, fills the void and forms a strong symbiosis with the manpower vi deficit of the private security domain of India. All skills that are prerequisites for a good security professional are inherently displayed by veterans (Dustin Salomon, 2021a). However, there remains a shortfall of manpower of about 30% with a potential to generate a large number of jobs in India (FICCI, 2016). The private security sector in India will need trained, disciplined and experienced manpower to lead and govern the industry as it grows. Despite the shortfall of manpower in the private security industry in India, there still exists a large gap in the number of military veterans joining the security domain in India. The gap could be possible due to lack of awareness or pre-conceived notions about the private security field amongst personnel who are retiring from service. Further, guards in India have traditionally been known as ‘Chowkidar’, which in ordinary parlance means a watchman or a gatekeeper. Gate-keeping, in the eyes of the Indian public, is generally perceived to be a petty-job devoid of any skills or cognition. With the growing complexity of societies, the watchman has transcended to ‘security guard’ or even to a higher level called ‘security professional’. Over last four decades or so, manned guarding in India has evolved from ‘Chowkidaari’ to ‘ManTech’ soon morphing to ‘TechMan’ before settling into full the blown TSM (Total Security Management) or TSS (Total Security Solution) format with the convergence of physical guarding, electronic security & surveillance, cyber security and internal threats as a packaged end-to-end service (CISS India, 2019). In summary, the role of private security has been upgraded to much more than a mere gatekeeper. There is a need for a better understanding of the partnership between vii Private Security Domain in India and Indian Military Veterans. More specifically, the following research questions need to be addressed: a) How is the private security industry in India suitable and lucrative as a second career by military veterans? b) What skills and qualities do veterans contribute to the Private Security industry? c) How do military veterans impact the Private Security domain in India? d) How do organisations in India stand to benefit by hiring military veterans in their private security? The proposed research has a long-term goal of providing a better understanding of the symbiotic relation between trained and experienced Indian Military Veterans (Dustin Salomon, 2021a) and the booming Private Security industry in India (FICCI, 2016). The aim of this research is to study the private security domain in India and how military veterans make an impact and/or contribute to this sector. The research will identify the additional skills and traits that veterans bring to private security. The research will also provide a reference to military personnel, who are in the process of retiring, to consider Private Security as a respectable second career. Finally, the research will also undertake a study on how Indian military veterans have shaped, lead and contributed to the Private Security Industry in India worth USD 23 billion (FICCI, 2016). Particularly, the study has the following objectives: a) What are the prospects of Private Security domain in India? viii b) To demonstrate that the Private Security Sector in India is a good second career option for Military Veterans and Agniveers. c) To identify the inherent skills that make military veterans good private security professionals. d) Future prospects of Private Security Industry in India. The outcome of this research will be helpful and valuable to Indian Military Veterans as well as the Private Security sector of India. If military veterans choose the private security domain in India as a second career, it may be responsible for providing employment to a large number of military veterans. In turn, the private security domain of India stands to benefit with the availability of highly trained and experienced personnel to lead the emerging industry. The research may directly contribute to the resettlement of many veterans and provide employment opportunity to a large number seeking a second career in India. The research will also impact the private security industry